Physiological and Psychological Factors in Determining the Criminal Responsibility of Minors - Ding, Yuedi (International Journal of Social Sciences and Public Administration, 2025)
This study explored the impact of physiological and psychological factors on the determination of minors’ criminal responsibility. Studies have shown that the development of adolescent brains lags behind the emotional system, making them more likely to make impulsive decisions and increasing the risk of illegal behavior. In addition, psychological maturity is closely related to physiological development, and lack of family support and mental health problems often lead to criminal behavior. In order to more accurately assess the criminal responsibility of minors, this study proposes to establish a dual-track identification model of "physiological + psychological assessment", emphasizing the application of neuroscience and psychology in judicial assessment to optimize the mechanism for determining juvenile criminal responsibility and promote the judicial practice goal of giving equal importance to education and assistance.